2016
DOI: 10.1016/j.jnucmat.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Processing used nuclear fuel with nanoscale control of uranium and ultrafiltration

Abstract: Current separation and purification technologies utilized in the nuclear fuel cycle rely primarily on liquid-liquid extraction and ion-exchange processes. Here, we report a laboratory-scale aqueous process that demonstrates nanoscale control for the recovery of uranium from simulated used nuclear fuel (SIMFUEL). The selective, hydrogen peroxide induced oxidative dissolution of SIMFUEL material results in the rapid assembly of persistent uranyl peroxide nanocluster species that can be separated and recovered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Figure also shows SAXS analysis of the aqueous phase, the clusters extracted into the organic phase, and the simulated U 32 . While clusters likewise form from SIMFUEL (as observed previously) and they transfer to the kerosene layer, there are some differences between the aqueous‐ and organic‐phase clusters, as discussed and elucidated below.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Figure also shows SAXS analysis of the aqueous phase, the clusters extracted into the organic phase, and the simulated U 32 . While clusters likewise form from SIMFUEL (as observed previously) and they transfer to the kerosene layer, there are some differences between the aqueous‐ and organic‐phase clusters, as discussed and elucidated below.…”
Section: Resultssupporting
confidence: 53%
“…For experiments performed by using SIMFUEL as a starting material, we suspended the SIMFUEL powder (50 mg) in water (0.6 mL), ammonium hydroxide (0.4 mL, 4 m ), and hydrogen peroxide (0.3 mL, 30 %), adapting the procedure from the prior study of Burns, who demonstrated filtration separation of uranium from the minor oxides in SIMFUEL . The majority of the UO 2 was rapidly oxidized, yielding a light brown (black and yellow mixed) suspension.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8] Among these clusters is one that comprises 60 uranyl moieties and bears a remarkable resemblance to the prototypical nanostructure buckminsterfullerene, C 60 . 9 Uranium oxide nanostructure materials are of interest for potential relevance to advanced nuclear technology, including processing 10 and degradation 11 of nuclear fuels. There is fundamental interest in understanding the driving forces for the formation of the bent uranyl peroxide cage nanostructures, and the nature of the bonding in them.…”
Section: -mentioning
confidence: 99%
“…They are known for their formation by self-assembly, structural diversity, as well as their wide-ranging potential and realized applications including but not limited to catalysis, sustainable energy, electronics, and sensors . Relatively recently discovered actinide POMs also have potential applications in recycling nuclear fuels , and fabrication of mixed oxide fuels . POMs are valuable models for studying structure-size-property relations such as aggregation behavior in solution because they are larger than most inorganic complexes but smaller than colloids and are dissolvable as macroanions in various solvents .…”
Section: Introductionmentioning
confidence: 99%